EPIDEMIOLOGICAL STUDY OF SPVD TRANSMISSION IN WEST BENGAL - B. SINHA,; J. TARAFDAR, (The Bioscan, 2014)
A preliminary worked on SPVD transmission and its relationship with weather parameters and vector population were conducted. The populations of vectors (Aphis gossypii, Myzus persicae and Bemisia tabaci) at 30 DAP were less in initially and later increased with days of maturation of sweetpotato cultivars. Variations in the vector population among different cultivars were observed. The SPVD incidences were ranges from 1.11 to 17.70 percent among the sweetpotato cultivars. At 30-90Days after planting (DAP) population of Aphis gossypi were ranges from 1.3 to 8.33 and for Myzus persicae it was 1.6 to 7.33. The population of Bemisia tabaci was observed higher in numbers (10.3 in 30DAP and 19.6 in 90DAP) than the other aphid vector population in sweetpotato cultivars. The peak population was observed during March for both the years (A. gossypi, M. persicae and B. tabaci). Multiple regression equation of vectors population with meteorological factors (Temperature, Relative humidity and rainfall) showed both significant and non significant results.